Pengembangan sistem informasi pengelolaan jadwal ‎rapat dengan metode Rapid Application Development ‎‎(RAD)‎ - Sholikin, Sholikin (Maliki Interdisciplinary Journal, 2023)
In this era of technology and industrial revolution 4.0, software is very important. Almost all activities and activities of society today use software. This includes government and private institutions and agencies. Every agency and institution must have a meeting schedule, be it between divisions or sections within the agency or meetings with other institutions to discuss certain needs. In this case, it is necessary to have an effective schedule management so that each schedule does not clash with each other. So far, the recording of meeting schedules is still using the old method, namely using books and is prone to loss so that it is not effective and efficient. Therefore, it is necessary to develop a meeting scheduling system that can provide solutions to overcome the problems above. The purpose of this software design is to minimize the risk of losing documents and assist agencies and institutions in scheduling meetings. In this meeting schedule management information system, users can easily to manage meeting schedules in a shorter time than using the old method.